1990
DOI: 10.1128/jcm.28.9.2139-2141.1990
|View full text |Cite
|
Sign up to set email alerts
|

Case report and seeded blood culture study of Brucella bacteremia

Abstract: Diagnosis of brucellosis requires prompt detection and identification of the coccobacillus for appropriate patient management, as the organism is associated with a potentially severe outcome. In a recent experience, an 18-year-old migrant farm worker presented at a local hospital with nonspecific symptoms. A significant Brucella titer of 2,560 was followed by the recovery of a gram-negative coccobacillus, subsequently identified as Brucella abortus, from subcultured 5-day-old BACTEC NR730 negative blood cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…In general, this culture system can be considered as very sensitive method for the detection of microbial contamination. Earlier studies have demonstrated detection rates down to one colony‐forming unit of fastidious bacteria by using this system 28,29 …”
Section: Discussionmentioning
confidence: 99%
“…In general, this culture system can be considered as very sensitive method for the detection of microbial contamination. Earlier studies have demonstrated detection rates down to one colony‐forming unit of fastidious bacteria by using this system 28,29 …”
Section: Discussionmentioning
confidence: 99%
“…Roiz et al [11], using the BacT/Alert system, reported that, in their experience, all nine cultures obtained from five patients yielded the organism [15], also using BACTEC 9240, recovered 93% of 97 isolates in 5 days. Zimmerman et al [16], using BACTEC NR 730, reported that the growth time of Brucella spp. was inversely related to the concentration of bacteria; and they found that if the concentration was 5-500 CFU/mL, B. melitensis growth in BACTEC NR 730 would be within 2 days, whereas 5-7 days would be required for detection if the concentration was lower than 5 CFU/mL.…”
Section: Discussionmentioning
confidence: 99%
“…As the result of effective infection control measures implemented by health authorities, brucellosis has become a rare disease in North America and parts of western Europe. Because of that, published experiences with modern blood culture techniques, and particularly with the BACTEC system, for the detection of Brucella organisms are limited to a few reports of small outbreaks of the disease among travelers to countries where brucellosis is endemic (3,9).…”
Section: Discussionmentioning
confidence: 99%